Double Transfer of Chirality in Organocopper‐Mediated bis(Alkylating) Cycloisomerization of Enediynes1. Issue 12 (19th February 2014) - Campolo, Damien; Arif, Tanzeel; Borie, Cyril; Mouysset, Dominique; Vanthuyne, Nicolas; Naubron, Jean‐Valère; Bertrand, Michèle P.; Nechab, Malek
Abstract An original synthesis of chiral benzofulvenes triggered by organocopper reagents is reported. These enantiopure products are available through a highly chemo‐, regio‐, diastereo‐, and enantioselective bis(alkylating) cycloisomerization process. A double chirality transfer (central‐to‐axial‐to‐central) is observed.